Kepemimpinan Transformatif Dalam Meningkatkan Kinerja Guru: Systematic literature review (SLR) - Mutoharoh Mutoharoh; Yuni Herlina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine in depth the role of transformative leadership of school principals in improving teacher performance through literature studies. Transformative leadership is one approach that is considered effective in facing today's educational challenges, especially in creating an innovative, collaborative and adaptive work environment. This study uses a literature review method by tracing various sources such as books, journals, and relevant scientific articles, both those that have been published in print and online. From the results of the search, it was found that Principals who implement transformative leadership are able to increase teacher motivation, competence, and professionalism. The strategies used include providing motivation, awards, involving teachers in decision-making and providing ongoing training and professional development. In addition, transformative leadership also plays a role in building a positive organizational culture and supporting learning innovation. However, the implementation of transformative leadership also faces various challenges such as resistance to change and limited resources. Therefore, ongoing efforts are needed to strengthen the leadership competence of school principals and support from all education stakeholders. The results of this study are expected to be a reference for practitioners and education researchers in developing effective leadership models to improve the quality of education by improving teacher performance.